Can teacher’s cognitive ability predict job performance?: a preliminary study - Robalino Guerra, Paulina Elizabeth (2020)
Matching candidates with particular jobs is one of the main purposes in the workplace. Previous research has shown that cognitive skills tests and bio data are the strongest predictors of job performance. The aim was to analyze how cognitive level predict job performance. We use a non-probabilistic sample of 79 elementary school teachers, ages between 21 and 58 years old (M= 33.44; SD= 8.38; female= 82%). We use a socio-demographic questionnaire; attentional network test (ANT), working memory capacity test (AOSPAN) and a job performance scale. The results show that attention and working memory reaction time are related with job performance, but just Working memory reaction time predict 5% of task performance. Results are consistent with previous studies. Limitations and new hypotheses will be discussed.